PENGEMBANGAN DESA EKOWISATA TERPADU SEBAGAI OPTIMALISASI POTENSI KAWASAN PANTAI PATEK BERBASIS UMKM DI DESA GELUNG SITUBONDO - Sulistyaningsih Sulistyaningsih; Sumarno Sumarno (Relawan Jurnal Indonesia, 2018)
Gelung village located in the district Panarukan, Situbondo, East Java province which has a huge potential in tourism and agriculture. Public awareness of the potential of tourism and farming village of Gelung need is developed as pathek beach tourism and seaweed farming as well as SMEs are mostly found in the village of Gelung. Looking at the problems and potential of the seed Gelung Village, held programs KKN-PPM help alleviate the problem, utilizing the potential of the village, and empower an optimal and sustainable. Problem solving and how empowerment can be achieved with the cooperation of all parties, both from the public, government agencies and non-government, community organizations. Results achievement KKN PPM program implementation including the increase in participation and performance in the production of seaweed farming communities and SMEs. improvement of people's skills through training for a variety of seaweed processing, knowledge of food diversification, improved agriculture in early childhood and increased tourism knowledge. In the long run this program KKN PPM is an increase in the Community empowerment through increased per capita income through touch economics / business, given the increase in the human development index increased knowledge and skill touch people in the village of Bun on participation, both male and female population.